Energy Retrofitting of a Buildings’ Envelope: Assessment of the Environmental, Economic and Energy (3E) Performance of a Cork-Based Thermal Insulating Rendering Mortar - Silvestre, José (2020)
This paper presents an environmental, economic and energy (3E) assessment of an energy retrofitting of the external walls of a flat of an average building with the most current characteristics used in Portugal. For this intervention, a cork-based (as recycled lightweight aggregate) TIRM (Thermal Insulating Rendering Mortar) was considered. The declared unit was 1 m2 of an external wall for a 50-year study period and the energy and economic costs and savings, as well as the environmental impacts, were analytically modelled and compared for two main alternatives: the reference wall without any intervention and the energetically rehabilitated solution with the application of TIRM. Walls with improved energy performance (with TIRM) show lower economic and environmental impacts: reductions from 6% to 32% in carbon emissions, non-renewable energy consumption and costs during the use stage, which depends on the thickness and relative place where TIRM layers are applied. A worse energy performance is shown by reference walls (without TIRM) during the use stage (corresponding to energy used for heating and cooling), while the improved walls present economic and environmental impacts due to the application of TIRM (including the production, transport and application into the building) that do not exist in the reference walls. The comparison between reference walls and energy-retrofitted ones revealed that reference wall become be more expensive when more demanding operational energy requirements are analysed over a 50-year period, even if renewable materials are more expensive.